Food Safety Behaviors of Hospitality Students In Malaysia: A Study On Knowledge, Attitude And Practice - Sulaiman, Suria; Zakaria, Nurul’Aishah; Hakim, Fairuz Abd; Mohd Asri, Dian Aszyanti Atirah; Halim, Faqihah Abdul; Mohamad Nizam, Muhammad Hafeezuddin (Journal of Islamic, Social, Economics and Development, 2025)
Foodborne illnesses continue to pose serious health risks, often stemming from poor hygiene, improper food handling, and limited food safety knowledge. Studies have shown that being well-informed about food safety can greatly reduce these risks, especially for those directly involved in preparing food. This study aims to understand how knowledge, attitudes, practices, and behaviour around food safety are connected, focusing on hospitality students in Malaysia who regularly handle food. An online survey gathered responses from 213 students, and the data were analyzed using SPSS software. The results reveal a statistically significant relationship between food safety knowledge and attitudes with behaviours, reinforcing the need for targeted educational interventions. The findings advocate for the integration of robust food safety training programs to cultivate responsible food handling practices and uphold public health standards. This research contributes to the growing body of literature emphasizing the pivotal role of informed and conscientious food handlers in reducing the incidence of foodborne illness.